How neural representations of newly learnt faces change over time: Event-related brain potential evidence for overnight consolidation - Wiese, Holger; Popova, Tsvetomila; Schipper, Maya; Zakriev, Deni; Burton, A. Mike; Young, Andrew W. (Cortex, 2024)
Previous experiments have shown that a brief encounter with a previously unfamiliar person leads to the establishment of new facial representations, which can be activated by completely novel pictures of the newly learnt face. The present study examined how stable such novel neural representations are over time, and, specifically, how they become consolidated within the first 24 h after learning. Using event-related brain potentials (ERPs) in a between-participants design, we demonstrate that clear face familiarity effects in the occipito-temporal N250 are evident immediately after learning. These effects then undergo change, with a nearly complete absence of familiarity-related ERP differences 4 h after the initial encounter. Critically, 24 h after learning, the original familiarity effect re-emerges. These findings suggest that the neural correlates of novel face representations are not stable over time but change during the first day after learning. The resulting pattern of change is consistent with a process of consolidation.
Keywords: Face recognition; N250; Consolidation; Event-related potentials; Face Learning